The Way People Lie in Markets: Detectable vs. Deniable Lies - Tergiman, Chloe; Villeval, Marie Claire (Management Science, 2023)
In a finitely repeated game with asymmetric information, we experimentally study how individuals adapt the nature of their lies when settings allow for reputation building. Although some lies can be detected ex post by the uninformed party, others remain deniable. We find that traditional market mechanisms, such as reputation, generate strong changes in the way people lie and lead to strategies in which individuals can maintain plausible deniability; people simply hide their lies better by substituting deniable lies for detectable lies. Our results highlight the limitations of reputation to root out fraud when a deniable lie strategy is available. This paper was accepted by Yan Chen, behavioral economics and decision analysis. Funding: Financial support from the Agence Nationale de la Recherche [Grant ANR-14-CE28-0010-01] and from IDEXLYON at Universite de Lyon (project INDEPTH) within the Programme Investissements d’Avenir of the Agence Nationale de la Recherche [Grant ANR-16-IDEX-0005] is acknowledged. This research also benefited from the support of the Laboratory of Excellence CORTEX of the Agence Nationale de la Recherche [Grant ANR-11-LABX-0042] of Universite de Lyon within the program Investissements Avenir operated by the Agence Nationale de la Recherche [Grant ANR-11-IDEX-007]. Supplemental Material: The data files and online appendix are available at https://doi.org/10.1287/mnsc.2022.4526 .